Contributo para a caracterização das raças serpentinas e charnequeira - Pinto, João Manuel Luciano Nunes da Silveira (2017)
Esta dissertação retoma um estudo com 49 cabras e 45 cabritos da raça Serpentina, 24 cabras e 28 cabritos da raça Charnequeira, exploradas em regime extensivo. Pretende ser um contributo para a caracterização destas raças. Com este objectivo calculou-se a fertilidade que foi de 92% nas duas raças e a prolificidade foi de 160% (62,5% partos duplos) na Serpentina e de 141% (57,1% partos duplos) na Charnequeira. A mortalidade dos cabritos, do nascimento até ao desmame, foi de 15,7%, na Serpentina e de 6,6%, na Chamequeira. Os pesos das cobrições ao parto, na Serpentina aumentaram 17% e 13,6% na Chamequeira, apresentando variações significativas na raça, mas não entre raças. Os cabritos de partos simples obtiveram maiores ganhos médios diários do nascimento ao desmame. Não houve variações significativas nos pesos entre machos e fêmeas. Analisaram-se 24 carcaças de cabritos, machos inteiros. O Rendimento Corrigido foi de 52% para as duas e a relação Músculo/Osso de 2,13 (Charnequeira) e 2,12 (Serpentina). O Índice Compacidade para a Charnequeira foi de 11,78 e 11,29 para a Serpentina, evidenciando esta melhor conformação. Definiram-se os seguintes cortes nas carcaças: I-Pá; II-Perna; III- Costela+Sela; IV-Aba; V-Pescoço. Analisou-se o músculo quanto à gordura, proteína, cálcio e fósforo. ABSTRACT: This dissertation retrieves a study involving 49 goats and 45 kids of Serpentina breed, 24 goats and 28 kids of Chamequeira breed exploited in an extensive management. It is intended as a contribution to the characterization of these breeds. To this end, various reproductive parameters were calculated. The fertility stood at 92% in both breeds and the prolificacy in the breed Serpentina was 160% (62.5% in twin births) and in the breed of Chamequeira was 141% (57.1% in twin births). We noted a mortality rate in kids from birth to weaning higher in the Serpentina breed (15.7%), while the Chamequeira breed recorded 6.6%. The evolution of the weights during the mating period to childbirth, increasing 17% in the Serpentina breed and 13.6% in Chamequeira breed. We noted significant variations in each breed, but not between each other. The kids resulting of simple birth had higher average daily weight gain from birth to weaning. We did not note significant variations of weight between males and females. We analysed the carcasses of 24 male kids. The corrected yield was 52% for both breeds and the muscle-bone ratio was 2,13 (Chamequeira) and 2,12 (Serpentina). The compactness index for the Chamequeira breed was 11.78 and 11.29 for the Serpentina breed, showing Serpentina breed had better conformation. We proposed the following cuts in the carcass: I-Shovel, II Leg, III- Rib +Sela, IV-Aba and V-Neck. We also analysed the muscle according to their fat, protein, calcium and phosphorus, aiming to show the dietary interest of this muscle.